Środowisko społeczne i szkolne ucznia a efektywność procesu nauczania i uczenia się języków obcych - Janicka, Monika (Neofilolog, 2011)
The paper is aimed at the identification of the environmental factors which have the most significant impact on the level of teenagers‟ compe-tence in foreign languages. The main goal is to determine whether school is capable of reducing the impact of adverse social background on achievement in learning a foreign language. The first part of the article is focused on the theoretical aspects of socialization related to the process of learning and provides an overview of research connected with the sub-ject. The second part presents the tools, procedures and findings of the author‟s own research project.